2016
DOI: 10.1016/j.bandc.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Music-induced changes in functional cerebral asymmetries

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 95 publications
(117 reference statements)
3
16
0
5
Order By: Relevance
“…The demonstration of these effects in the FC3/FC4 site is consistent with previous findings ( Davidson et al, 1990 ; Jackson et al, 2003 ; Travis and Arenander, 2006 ; Kline and Allen, 2008 ; Dennis and Solomon, 2010 ), although meaningful findings are also commonly obtained from data collected from the F3/F4 site (see Schmidt and Trainor, 2001 ; Thibodeau et al, 2006 ), which was not observed in the current study. The asymmetry findings also verify findings observed in response to positive and negative emotion induction by music ( Schmidt and Trainor, 2001 ; Altenmüller et al, 2002 ; Flores-Gutierrez et al, 2007 ; Hausmann et al, 2013 ). Importantly, no significant FA effect was observed in the control P3/P4 sites, which is an area not implicated in emotional responding.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The demonstration of these effects in the FC3/FC4 site is consistent with previous findings ( Davidson et al, 1990 ; Jackson et al, 2003 ; Travis and Arenander, 2006 ; Kline and Allen, 2008 ; Dennis and Solomon, 2010 ), although meaningful findings are also commonly obtained from data collected from the F3/F4 site (see Schmidt and Trainor, 2001 ; Thibodeau et al, 2006 ), which was not observed in the current study. The asymmetry findings also verify findings observed in response to positive and negative emotion induction by music ( Schmidt and Trainor, 2001 ; Altenmüller et al, 2002 ; Flores-Gutierrez et al, 2007 ; Hausmann et al, 2013 ). Importantly, no significant FA effect was observed in the control P3/P4 sites, which is an area not implicated in emotional responding.…”
Section: Discussionsupporting
confidence: 86%
“…The pattern of data in these studies suggests that this frontal lateralization is mediated by the emotions induced by the music, rather than just the emotional valence they perceive in the music. Hausmann et al (2013) provided support for this conclusion via mood induction through a musical procedure using happy or sad music, which reduced the right lateralization bias typically observed for emotional faces and visual tasks, and increased the left lateralization bias typically observed for language tasks. A right FA pattern associated with depression was found to be shifted by a music intervention (listening to 15 min of ‘uplifting’ popular music previously selected by another group of adolescents) in a group of adolescents ( Jones and Field, 1999 ).…”
Section: Introductionmentioning
confidence: 81%
“…For example, although language lateralisation has been assumed to be a trait characteristic of the human brain, several studies found developmental changes in the degree and sometimes even the direction of the RVF/LH language advantage (e.g., Bishop, 2013). Even in adults, it has been shown that the LVF/RH advantage in verbal VHF tasks can change within relatively short-term intervals (e.g., Hausmann et al, 2002;Hausmann, Hodgetts, & Eerola, 2016;Mohr, Michel, et al, 2005), which might explain some of the observed intra-and inter-individual differences in language lateralisation.…”
Section: Introductionmentioning
confidence: 99%
“…A potential reason for this heterogeneity in the literature might be the lack of ecological validity in emotion research as the most prevalent method of positive or negative emotional induction is via movies, pictures or music (e.g. Gross & Levenson, 1995;Hausmann, Hodgetts, & Eerola, 2016;Hewig et al, 2005;Uhrig et al, 2016). Thus, emotions are largely only perceived during experimental paradigms.…”
Section: Introductionmentioning
confidence: 99%